The Role of Security Perception and Usage Impact of Mobile Accounting Applications - Isna Ardila; Masta Sembiring; Rini Astuti (Jurnal Akuntansi, 2025)
This study aims to measure the implementation of the Technology Acceptance Model (TAM) in using Mobile Accounting Applications on smartphones by adding security perceptions as an external variable. This study integrates the variables of perceived usefulness and ease of use to explain the factors influencing technology acceptance. The quantitative survey method analyses the relationship between variables through hypothesis testing. Primary data were obtained from 60 MSME owners in Medan City through online questionnaires and analysed using SmartPLS4 with the SEM model. The results showed that security perceptions affect perceived usefulness and ease of use, which affect attitude. In addition, the attitude positively affects behavioural intention, ultimately affecting the application's actual use. This study provides important insights into the factors influencing the adoption of accounting application technology among MSMEs.